A new species of Procestus Townes (Hymenoptera: Ichneumonidae: Banchinae) from Brazil - Herrera-Flórez, Andrés Fabián; Penteado-Dias, Angelica (Zootaxa, 2021)
A new species of Procestus Townes, 1970 is described from Brazil. An identification key to all known species is provided. Figures of the holotypes of Procestus nabis Townes, 1970 and P. simplex Townes, 1970, and a paratype of P. pammae Ugalde & Gauld, 2002 are included. Procestus nabis and P. simplex are redescribed.